ESG-ORIENTED INVESTMENTS IN THE INSURANCE SECTOR: CHALLENGES AND PROSPECTS FOR UKRAINE - ZAIACHKIVSKA, oksana; KOTYK, Olha; FEDORCHUK, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the study of modern ESG-oriented investments in the financial activities of insurance companies, which include environmental, social and governance factors. The purpose of the article is to identify the essence of the concept of "ESG-investing" and the main features that distinguish it from other types of investment. The article considers the importance of ESG for investors and financial markets, as ESG factors are becoming increasingly important criteria when making investment decisions and assessing risks. The analysis of the positive and problematic aspects of the «White Paper» on the insurance market is carried out, and the prospects and challenges for the implementation of RM2 approaches in the context of ESG-risks are also outlined. Among the positive aspects, we can mention such as, a systemic vision of ESG-risks, orientation on forward-looking approaches, institutionalization of the role of the risk manager, and the possibility of adaptation to the scale of the company. The NBU recognizes that there is no universal standard, and expectations for large, medium and small companies will be differentiated. This reduces the risk of excessive administrative pressure and allows for the implementation of the principle of proportionality — an important principle of both RM2 and modern supervision, strengthening the connection between risk management and strategy, and connecting with international practice. The document is built taking into account the recommendations of the EBA, EIOPA, TCFD and other international structures. This allows Ukrainian insurers to simultaneously meet the requirements of the regulator and be competitive in the international context, a transparent approach to forming expectations, emphasizing the role of associations and self-regulation, creating a basis for real scenario analysis, understanding ESG not only as a challenge, but as a driver of competitiveness. The problematic aspects and risks of implementing the White Paper are the high level of abstraction of some formulations, the lack of instructions for specific processes, the lack of a clear ESG code for the insurance industry, excessive attention to climate aspects, insufficient specificity in interaction with supervisory authorities, the lack of connection with the current regulatory framework, etc. Therefore, the focus is on assessing the positive and problematic aspects of the White Paper regarding the insurance market, as well as outlining the prospects and challenges for implementing RM2 approaches in the context of ESG risks. And it is ESG approaches — if implemented correctly — that are able to identify these problems before they become systemic.
Keywords: ESG investments; insurance companies; «White Paper»